2008
DOI: 10.1007/s10719-008-9205-x
|View full text |Cite
|
Sign up to set email alerts
|

The unique enzymatic function of field bean (Dolichos lablab) d-galactose specific lectin: a polyphenol oxidase

Abstract: The polyphenol oxidase (PPO) of field bean (Dolichos lablab) is a tetramer made up of two subunits of mass 29,000 and 31,000 Da. The amino acid sequence of the tryptic peptides showed approximately 90% sequence identity to the D: -galactose specific legume lectins. The haemagglutinating activity of a pure and homogenous preparation of PPO measured using human erythrocytes was 1261 HAU mg(-1) protein and was inhibited by D: -galactose. Purification by galactose-sepharose chromatography also indicated that the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Dolichos lablab , commonly known as field bean, is a leguminous plant largely grown in India. Field bean seeds contain one glucose/mannose‐specific lectin (DLL‐I) and a galactose/N‐acetyl‐ d ‐galactosamine (GalNAc)‐specific lectin (DLL‐II) . DLL‐II is a tetrameric protein with two subunits of masses 29 and 31 kDa, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dolichos lablab , commonly known as field bean, is a leguminous plant largely grown in India. Field bean seeds contain one glucose/mannose‐specific lectin (DLL‐I) and a galactose/N‐acetyl‐ d ‐galactosamine (GalNAc)‐specific lectin (DLL‐II) . DLL‐II is a tetrameric protein with two subunits of masses 29 and 31 kDa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Kanade et al. [5] characterized DLL‐II and found that unlike the typical lectins, DLL‐II and also the closely related DBL—a lectin from Dolichos biflorus —have relatively weaker binding affinities for their sugar ligands . However, a distinctive moonlighting function of DLL‐II is a high polyphenol oxidase (PPO) activity that oxidizes diphenols to o‐quinones (EC 1.10.3.1) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations